Visualizing designer quantum states in stable macrocycle quantum corrals - Xinnan Peng (Nature Portfolio, 2021)
Creating atomically-precise quantum architectures with high digital fidelity and desired quantum states is an important goal for quantum technology applications. Here the authors devise an on-surface synthetic protocol to construct atomically-precise covalently linked organic quantum corrals with the formation of a series of new quantum resonance states.